DETECTIVE FORMULA IN AGATHA CHRISTIE’S DEATH ON THE NILE - Ratu, Natsha A. A.; Wuntu, Ceisy N.; Maukar, Merlin (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research employs a qualitative research design to investigate the application of the Detective Formula in Agatha Christie’s mystery novel, Death on the Nile. Emphasizing the main character’s problem-solving abilities, the study was made in qualitative approach, as the data acquired are in the from of words. Qualitative research aligns with the study’s objective of analyzing the intricacies of detective methodologies within the narrative.In this context, the researcher use qualitative methods to extract insights from books, movies, and internet soursces. This qualitative research not only in the literary merit of Christie’s work but also contributes nuanced perspective research is grounded in the nature of the data, which is primarily textual and visul, allowing for a descriptive analysis of classic detective fiction.this study will be focused on the detective formula in Death on the Nile by Agatha Christie. In the context of the research background outlined above, the study aims to explore the application of the Detective Formula in problem-solving within Agatha Christie’s Death on the Nile. This inquiry examines the actions and strategies undertaken by the main character as they address challenges while solving the cases presented in the novel. The objective is to analyze the protagonist’s approach, methods, and decision-making processes, providing insights into how they navigate and resolve complex mysteries within the novel.